2014
DOI: 10.1042/bst20140070
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt-mediated regulation of p53 in cancer

Abstract: Mutations activating the PI3K (phosphoinositide 3-kinase)/Akt signalling pathway and inactivating the TP53 tumour-suppressor gene are common mechanisms that cancer cells require to proliferate and escape pre-programmed cell death. In a well-described mechanism, Akt mediates negative control of p53 levels through enhancing MDM2 (murine double minute 2)-mediated targeting of p53 for degradation. Accumulating evidence is beginning to suggest that, in certain circumstances, PTEN (phosphatase and tensin homologue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 78 publications
(83 reference statements)
5
122
0
Order By: Relevance
“…Additionally Akt activates FOXO3a to inhibit apoptosis and increase mitochondrial biogenesis to support a growing cell [23]. The PI3K/Akt signaling pathway is essential for normal cellular function, and commonly this pathway is mutated and hyperactivated in cancer models [24]. Thus activation of Akt triggers increase in cell size, enhanced glycolytic activity and metabolism, as well as cell survival [25].…”
Section: The Debate Regarding the Initiating Events Of Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally Akt activates FOXO3a to inhibit apoptosis and increase mitochondrial biogenesis to support a growing cell [23]. The PI3K/Akt signaling pathway is essential for normal cellular function, and commonly this pathway is mutated and hyperactivated in cancer models [24]. Thus activation of Akt triggers increase in cell size, enhanced glycolytic activity and metabolism, as well as cell survival [25].…”
Section: The Debate Regarding the Initiating Events Of Cancermentioning
confidence: 98%
“…This evidence suggests that the genetic dysfunction that is found in cancer cells is causatively due from a secondary consequence to mitochondrial dysfunction. p53 and cancer p53 is a cellular regulator and transcriptional factor with tumour suppressor properties which is an important regulator of cell death and replicative senescence in response to oncogenic stress [24]. It is often described as the 'guardian of the genome'.…”
Section: The Debate Regarding the Initiating Events Of Cancermentioning
confidence: 99%
“…The increased potential for cellular proliferation leading towards tumorigenesis initiated through PKB activation may also result from a response towards various cellular stimuli, such as heat shock, osmotic, and oxidative stress [229]. Mechanistic research has revealed a wide range of influences [231], including critical roles by AKT in proliferation [232], resistance to apoptosis [233], glucose metabolism [234], cell migration, [235] and the regulation of autophagy [236]. …”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…S8a). AKT1 is a member of AKT signaling and it is known that active AKT signaling mediates degradation of the tumor suppressor TP53 (Abraham et al , 2014). Hence, overexpression of AKT1 could be the cause of TP53 downregulation.…”
Section: Resultsmentioning
confidence: 99%